Interaction mechanism of poly (o-ethoxyaniline) and collagen blends - Piza, M. A.; Constantino, CJL; Venancio, E. C.; Mattoso, LHC (Elsevier B.V., 2003)
Blend films of poly (o-ethoxyaniline) (POEA) and collagen were fabricated by casting under optimized conditions and characterized by Raman scattering and UV-vis absorption spectroscopies. The UV-vis spectra showed that the addition of collagen in the aqueous solution of POEA promotes a dedoping of the POEA. This effect was also observed for the blend films as supported by Raman scattering and a mechanism for the chemical interaction between POEA-collagen is proposed. The influences of different percentage of collagen as well as the pH of stock solutions during the fabrication process of the blend films were also investigated. It was found that the preparation method plays an important role in the flexibility and freestanding properties of the films. Complementary, the surface morphology was studied by atomic force microscopy and the conductivity by dc measurements. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: conducting polymer; collagen; blend